Striations at The Base of The Paleo-Fan and Channel Revealed by 3D Seismic Data, Offshore Cameroon - Anh Ngoc Le (Indonesian Journal on Geoscience, 2021)
DOI: 10.17014/ijog.8.1.101-107The 3D seismic data, offshore Cameroon, reveal the evidence of a Pliocene fan and a channel with a series of striations at their base. The fan and channel developing in Early Pliocene, were characterized by high amplitude reflections with bi-directional downlap on the base of the Pliocene sequence, and interpreted to be deep-water sandrich fan and channel. Pliocene channel flowed from east to west in the High Gradient Slope (HGS), whereas, the fan extended from NE to SW on the Low Gradient Slope (LGS). Individual striations have been imaged that are 20 - 50 m wide, c. 10 - 20 km long, and 4 - 8 m deep, trending NE - SW and E - W, slightly divergent patterns toward downslope. Striations are observed at the base of fan and channel suggesting the beginning of a period of unstable slope creating NE - SW slides in LGS and erosion in HGS. They were followed by the deposition of large scale fan deposits on the LGS and a series of parallel aggradational channels in the HGS. The striated unconformity at the base of the Pliocene sequence may be the result of a major tectonic uplift event or significant climate changes.